Karakter Dan Pola Tata Ruang Kawasan Sekitar Kampus Universitas Brawijya - Ramdlani, Subhan; Soekirno, Ali; Sri Giriwati, Novi Sunu (Jurnal Ruas, 2013)
The Surrounding of UB campus are an area affected directly or indirectly by the development of UB. The developments of the campus will be more or less influence to the spatial development of this area. Conversely, the dynamics that occur in this area will be an important input in the development of the upcoming campus. From this point, the purpose of this study was to identify the characteristics and spatial surrounding area of UB campus as patterns of land use that fit by the character. By studying and understanding the existing conditions, the results are expected to be used as one of the "database" or even "input" in determining the direction of development of the UB campus. That will create a harmonious environment and mutual support between the UB campus and the surrounding. To achieve these objectives, this study used a qualitative descriptive method. Observations and studies carried out on spot-spot patterns of land use in the area surrounding the campus, a block of residential, open space, other infrastructure spread over several areas around campus UB (UB). Thus, gain characteristics (structure, shape and space) and the spatial pattern of the area of study materials to explain the link with the development of the UB campus layout.Keywords: character, layout, campus.